Children’s self-regulation and coping strategies in a frustrated context in early education - Jouni Veijalainen; Jyrki Reunamo; Nina Sajaniemi; Eira Suhonen (South African Journal of Childhood Education, 2019)
Background: A large body of earlier research has focused on studying children’s self-regulation (SR) skills and frustration with different methods. However, considerably less attention has been given to hearing children’s own voice. The current study sought to demonstrate children’s own comprehension and highlight it as a valuable and unique tendency to fill the scientific gap in the research area.